Determinants of Premarital Sex Behavior: Application of Theory of Planned Behavior and Social Cognitive Theory - Nur Laili Qomariah; Eti Poncorini Pamungkasari; Uki Retno Budihastuti (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Health problems in adolescents are among the most important problems in the human life cycle, especially reproductive and sexual problems. Actively conducted premarital sex behavior poses a risk to teenage pregnancy and transmission of sexually transmitted diseases. This study aims to analyze the theory of planned behavior and social cognitive theory on the determinants of premarital sex behavior in adolescents.Subjects and Method: This was a cross-sectional study design. The study was conducted at 25 high schools/vocational high schools in Gresik, East Java, from September to October 2020. A sampling of 200 adolescents used stratified random sampling and simple random sampling. The dependent variable was premarital sex behavior. The independent variables were the intention, attitude, subjective norms, peer support, family intimacy, and self-efficacy. The data were collected by using a questionnaire. Data were analyzed using multiple logistic regression with Stata 13.Results: Premarital sexual behavior increased with strong intention (b= 1.06; 95% CI= 0.15 to 1.98; p= 0.015), positive attitude (b= 1.22; 95% CI= 0.38 to 2.13; p= 0.009), subjective norms supportive (b= 1.09; 95% CI= 0.14 to 2.04; p= 0.024), and strong peer support (b= 1.37; 95% CI= 0.44 to 2.30; p= 0.004). Premarital sexual behavior decreased with strong family intimacy (b= -1.32; 95% CI= -2.23 to -0.40; p= 0.005) and strong self-efficacy for abstinence (b= -1.03; 95% CI= -2.23 to -1.93; p= 0.025). There was an effect at the school level on premarital sex behavior with ICC 24.6%.Conclusion: Premarital sexual behavior increases with strong intentions, positive attitudes, supportive subjective norms, and strong peer support. Premarital sexual behavior decreases with strong family intimacy and strong abstinence self-efficacy. There is an effect at the school level on premarital sexual behavior.Keywords: premarital sex behavior, theory of planned behavior, social cognitive theory, adolescents.Correspondence: Nur Laili Qomariah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126. Email: lailiqomar@gmail.com. Mobile: +6281234190160.Journal of Health Promotion and Behavior (2020), 05(04): 272-283https://doi.org/10.26911/thejhpb.2020.05.04.05.